The impact of blood lactic acid levels on retinopathy of prematurity morbidity - Congcong Zhao; Zhihong Sun; Hongming Chen; Kaili Li; Huiqing Sun (BMC Pediatrics, 2024)
Abstract Background Retinopathy of prematurity (ROP) is a common disease in premature infants. In recent years, most researchers have used lactic acid as poor prognosis marker in premature infants. This study aims to explore investigate the impact of blood lactic acid levels on ROP. Methods A retrospective case-control study was conducted, and infants with severe ROP born with birth weight (BW) ≤ 1500 g and gestational age (GA) ≤ 32 weeks were enrolled from November 2016 to November 2021. Infants without any stage ROP were included as controls and were matched with ROP infants (1:2) by GA and BW. All selected preterm infants were tested for heel terminal trace blood gas analysis within two weeks of life. Changes in blood lactic acid levels in the two groups were compared and analyzed by using multivariate logistic regression analysis. Sensitivity and specificity were analyzed by receiver operating characteristic (ROC) curve. Results There were 79 infants in ROP group, and 158 infants in control group. The levels of blood lactic acid were significantly higher in the ROP group on days 1, 3, 5, and 7 compared with control group (all p < 0.05). The blood lactic acid levels on day 5 was an independent risk factor for ROP (p = 0.017). The area under the curve (AUC), sensitivity and specificity were highest on day 5 (AUC 0.716, sensitivity 77.2% and specificity 62.0%, respectively, p < 0.001), and higher on days 1, 3, and 7. Conclusion A high blood lactic acid level in the first seven days of life may be associated with increases ROP occurrence in very preterm infants, and suggest blood lactic acid level may impact the occurrence of ROP.